22 Housing Need Amongst Children with Medical Complexity: A Cross-Sectional Descriptive Study of Three Populations. (29th October 2021) - Esser, Kayla; Moore, Clara; Hounsell, Kara Grace; Davis, Adrienne; Sunderji, Alia; Shulman, Rayzel; Cohen, Eyal; Orkin, Julia
Abstract: Primary Subject area: Complex Care Background: Children with medical complexity (CMC) have medical fragility, complex chronic disease necessitating specialized care, functional disability, and/or high technology dependence. Housing is an important social determinant of health, yet research on prevalence and types of housing need in CMC is limited. Housing need encompasses unstable (frequent moves), inaccessible (lack of ramps/lifts), inadequate (major repairs needed), unsuitable (not enough bedrooms), or unaffordable housing. Given the association between housing and health, housing need may be an important consideration when caring for CMC. Objectives: The primary objective was to describe the prevalence of and factors related to housing need in CMC. The secondary objective was to compare housing need between CMC, children with one chronic condition (Type 1 diabetes; CT1D) and healthy children (HC) to understand the relationship between chronic conditions and housing need. Design/Methods: This was a cross-sectional descriptive study. Housing affordability, adequacy, suitability, stability, and accessibility were evaluated through surveys administered to caregivers of CMC, CT1D, and HC at a tertiary-care paediatric hospital using convenience sampling. The association of binary outcomes of housing need between groups was analyzed using logistic regression models, adjusting for sociodemographic factors (income, education, employment, geography, immigration status). Results: 453 caregivers participated (Table 1). Compared to caregivers of HC, caregivers of CMC had higher odds of reporting one or more moves in the last two years (1.3 times), having safety concerns (3 times), using a common area as a bedroom (5.2 times), and experiencing housing stress (3.2 times), after sociodemographic factors were adjusted for (Table 2). Families of CT1D also had elevated odds of some indicators of housing need compared to HC, although to a lesser extent than CMC. 62.2% of CMC indicated they had to reduce spending on basics in order to afford their rent/mortgage, compared to 35.9% of CT1D and 25.2% of HC. Nearly two-thirds of CMC (60.2%) reported a need for accessibility accommodations in their home. Of those who installed accommodations, 62.9% felt the installations were a financial burden (cost ranged from $800-$80, 000). Conclusion: Families of CMC had higher odds of reporting unstable, inadequate, unsuitable, and stressful housing compared to HC even after sociodemographic factors were accounted for, suggesting an association between complexity of child health conditions and housing need. Access to appropriate housing may improve the health of CMC. Health care providers can screen for housing need, become familiar with housing interventions, and advocate for improved resources to address housing need in CMC.